The Domains of Cross-Cultural Adjustment: An Empirical Study with International Students - Campos, Joana; Pinto, Luisa Helena; Hippler, Thomas (Journal of International Students, 2021)
This study examines the dimensionality of a new measure of international students’ adjustment using a sample of 189 international students. Drawing on earlier conceptualizations of cross-cultural adjustment as a person-environment fit and a previous scale measuring adjustment from the expatriate literature, this study shows that this scale can be meaningfully adapted to the higher education context. Confirmatory factor analyses identified a stable 8-factor structure with adequate psychometric properties. Descriptive analysis confirms that international students are fairly adjusted in a number of distinct domains. The findings also provide criterion-related validity by showing positive associations between host social interaction and host connectedness and students’ adjustment. This study contributes to the literature by offering a theoretically based scale that assesses international students’ adjustment on a wide range of dimensions. It puts forward a useful tool for higher education counsellors and support services to monitor international students’ adjustment and avoid adjustment difficulties.